Intelligent challenges of technology and organization of machine manufacturing processes - Kałkowska, Joanna (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
Intelligent aspects of challenges facing the technology and organization of machines production in the near future (microbuses and buses) relate to adaptive understanding, learning and the use of knowledge and skills in changing operational conditions. The turbulence and unpredictability of these conditions are a sources of agility problems that are not effectively algorithmizable. Solving them requires the use of eight digitizing challenges of the Industry 4.0. The research presented in the article uses two sets of heuristic methods: the Delphi method and its quasi-morphological effect as well as comprehensive brainstorming. Research conclusions emphasize, among others, the requirement of changing the classic rules of organizational professionalism, the risk-related challenges of a sustainable ecosystem as well as the need to “demystify” of intelligent systems.